2007
DOI: 10.1051/alr:2007034
|View full text |Cite
|
Sign up to set email alerts
|

Growth performances of juvenile soleSolea soleaunder environmental constraints of embayed nursery areas

Abstract: -Tidal embayments in the Bay of Biscay (France) host nursery grounds where common sole, Solea solea, is the most abundant flatfish species. This study aimed to appraise the way those habitats function as nurseries through juvenile sole's responses in somatic growth and condition (Fulton's K) during their first year of occupancy. Field data, two yearly trawling series, taken monthly, were compared with a 6-month-long mesocosm experiment involving reared fish of the same wild origin. Growth rates were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
(23 reference statements)
3
11
1
2
Order By: Relevance
“…There was no sign of food limitation in both tidal ponds and these mesocosms provide temperature and salinity similar to near shore waters. In addition growth rates of unexposed fish were similar to those reported in situ (Amara et al 2001) or in previous experiments in tidal ponds (Laffargue et al 2007). Since temperature and food are the two most important factors governing fish growth (Fonds 1979) the growth reduction of exposed fish in this study is likely to be related to their exposure to fuel oil and to impaired ability to allocate energy to growth.…”
Section: Reduced Biological Performances At Individual Levelsupporting
confidence: 88%
See 1 more Smart Citation
“…There was no sign of food limitation in both tidal ponds and these mesocosms provide temperature and salinity similar to near shore waters. In addition growth rates of unexposed fish were similar to those reported in situ (Amara et al 2001) or in previous experiments in tidal ponds (Laffargue et al 2007). Since temperature and food are the two most important factors governing fish growth (Fonds 1979) the growth reduction of exposed fish in this study is likely to be related to their exposure to fuel oil and to impaired ability to allocate energy to growth.…”
Section: Reduced Biological Performances At Individual Levelsupporting
confidence: 88%
“…Juvenile sole growth in the control pond followed well known patterns (Laffargue et al 2007), with high growth rate in summer then low values between D63 and D109, characteristic of a growth stop related to both reduction in temperature at the end of the summer growing season for Solea solea (Amara et al 2001) and lower photoperiod action on hormonal levels (Laffargue et al 2007). On the contrary, exposure to fuel-oil for as little as 24 hours had inhibited growth in flatfish juveniles.…”
Section: Reduced Biological Performances At Individual Levelmentioning
confidence: 79%
“…The average seawater temperature recorded with the CTD off Gran Canaria Island at 5 and 60 m depth was, respectively, 19 and 18.5 ºC in late winter, rising to 24.5 and 21 ºC in summer. This rise in water temperature could introduce changes in the metabolic activity of fish during spring and summer and could be the main factor responsible for opaque ring deposition (Laffargue et al 2007, Matta et al 2010. Félix et al (2011) indicated that temperature is one of the most important factors in growth of the flatfishes since it plays an important role in metabolism regulation.…”
Section: Figura 4 Curva De Crecimiento Estacional De Von Bertalanffymentioning
confidence: 99%
“…La formación de anillos de crecimiento observada en los otolitos sagita examinados en el presente trabajo parece estar íntimamente relacionada con la temperatura del mar (Nash y Geffen 2005, Laffargue et al 2007. Durante el invierno la Figure 5.…”
Section: Figura 4 Curva De Crecimiento Estacional De Von Bertalanffyunclassified
See 1 more Smart Citation